2012
DOI: 10.1055/s-0031-1299707
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Pheochromocytoma and Paraganglioma: Focus on Therapeutics

Abstract: Metastatic pheochromocytomas and paragangliomas are rare and challenging tumors. The tumor burden, combined with excessive catecholamine production, predispose to a broad spectrum of complications that range from spinal cord compression to any organ damage, all of which may lead to decreased quality of life and overall survival. Current therapies include surgery, systemic chemotherapy and radiopharmaceutical agents. Surgery is often a preferred therapy because it may cure or allow a long-term remission in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 42 publications
2
81
0
6
Order By: Relevance
“…Also, for the progressive spinal MPG, 3 cases receiving revision surgery showed the increase of Ki-67 index which may indicate the positive association between the Ki-67 and the possibility of metastasis. In our cohort, 13 primary PG specimens were bigger than 5 cm in maximum diameter which accorded with reports that bigger than 5 cm was more likely to transfer to malignancy and metastasis [7,10].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, for the progressive spinal MPG, 3 cases receiving revision surgery showed the increase of Ki-67 index which may indicate the positive association between the Ki-67 and the possibility of metastasis. In our cohort, 13 primary PG specimens were bigger than 5 cm in maximum diameter which accorded with reports that bigger than 5 cm was more likely to transfer to malignancy and metastasis [7,10].…”
Section: Discussionsupporting
confidence: 91%
“…1 accounting for 66.7% of all our cases. Metastasis could be presented at the time of diagnosis of the PG or years later [7,14] and the mean duration from surgical resection of the primary tumor to spinal metastasis was 8.2 (0.5-15) years. As a result, long-term follow-up was recommended for patients who had the PG treatment history, especially retroperitoneal ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of a PPGL-related somatic mutation in the tumour of a germ line 'negative PPGL' suggests sporadic disease, and, consequently, averts the need for screening the patient's relatives. Moreover, identification of a somatic mutation provides insights into tumour biology, and might guide targeted therapies, especially in patients with metastatic disease (when treatment options are limited) [56][57][58][59] . The Study Group recommends that the analysis of somatic mutations in PPGLs be carried out whenever possible.…”
Section: Somatic Variantsmentioning
confidence: 99%
“…Radiotherapy with 131 I-MIBG is an option if patients have a good uptake of 123 I-MIBG in active metastases. In addition, systemic chemotherapy has also been used to treat metastatic disease; however, the number of patients in these studies was too less to draw evidence-based conclusions (Adjalle et al 2009, Plouin et al 2012. A recent study on two mouse PCC cell lines showed that a combination of drugs that specifically block mTORC1/2, PI3K, ERK1/2, AKT, VEGF and EGF receptor functions can have a significant effect on the growth of these tumour cells.…”
Section: Introductionmentioning
confidence: 99%